Comparison of Emergency Department Visits for Complications of Gastrostomy Versus Gastrojejunostomy Tubes in Children. Issue 10 (October 2017) - Ronning, Meghann Marie; Gaillard, Philippe; Wey, Andrew; Roback, Mark G.
Abstract : Objectives: This study aims to evaluate frequency, type, and cost of gastrostomy tube (GT) versus gastrojejunostomy tube (GJT) complications in children presenting to the emergency department (ED). Methods: Patients were selected by electronic health record search for International Classification of Diseases, Ninth Revision, and procedure codes for GTs and GJTs/jejunostomy tubes. All children aged less than 18 years with GTs or GJTs placed during a 5-year period (2007–2012) at the University of Minnesota Masonic Children's Hospital were identified for retrospective review. Comparisons were made on demographic data, number and type of complications, and interventions performed for ED visits, which were abstracted from the electronic health record. Cost data were abstracted from the financial data system. Results: A total of 161 GT and GJT patients were identified; 31 children had 43 ED visits for complications. Ages ranged from 1 month to 17 years; median, 12 months; mean, 5.4 years; 25 (58%) were male, and 18 female (42%). Complications occurred in 15 GT (48.4%) and 16 GJT (51.6%) patients. The most common ED presenting complication was dislodgement, which occurred in 14 GTs (67%) and 18 GJTs (82%), followed by clogging 6 GTs (29%) and 1 GJTs (4.5%). Those presenting to the ED with GJT complications had higher mean overall charge (US $1987.00 vs US $913.10, P = 0.05). Conclusions: Although GTs and GJTs had similar rates of complications and ED visits, GJT complications were more likely to result in hospital admission and intervention by radiology, require specialist involvement, and have a higher cost charged to the patient.